Optimization of combustion generated particulates in a residual fuel-fired furnace - Raju, G.; Mustafa, Azeman (1991)
This paper is concerned with the experimental work carried out in a horizontal tunnel type furnace to study the optimization of production of particulates during the process of combustion and to find out whether or not this optimization is achieved at the expense of thermal efficiency of the furnace. The furnace was fired with the residual fuel oil of viscosity 3500 seconds Redwood 1 using industrial burners. Thermal input to the furnace was varied between 3MW and 4MW. During the plant trial, the influence of combustion air preheat, quantity of atomizing steam, swirl in the combustion air and oil-water emulsion firing on combustion generated particulates and thermal efficiency of the furnace was studied. The tests result showed that the operating parameters and added water in the emulsion fuel played an important role in the formation of particulates and heat transfer to the furnace cooling load.